Neonatal physiological and behavioral stress during neurological assessment - Sweeney, Jane K; Blackburn, Susan (The Journal of perinatal & neonatal nursing, 2013)
Physiological and behavioral effects of evaluative handling procedures were studied in 72 newborn infants: 36 preterm (30-35 weeks of gestation) and 36 full-term neonates (39-41 weeks of gestation). While the neurological assessment was physiologically and behaviorally destabilizing to both age groups, preterm subjects had higher heart rate (P < .001), greater increase in blood pressure (P < .01); decreased peripheral oxygenation inferred from mottled skin color (P < .001); and higher frequencies of finger splay (P < .001), arm salute (P < .01), hiccoughs (P < .001), and yawns (P < .001) than full-term subjects. Both groups demonstrated greater stress during the neuromotor phase of testing. Neonatal care professionals must scrutinize the diagnostic benefit, reliability, safety, and timing of neurological assessment given expected physiological and behavioral changes in stable preterm neonates.